Thermoelectric figure of merit of bulk FeSi2–Si0.8Ge0.2 nanocomposite and a comparison with β-FeSi2. (February 2015) - Mohebali, Milad; Liu, Yin; Tayebi, Lobat; Krasinski, Jerzy S.; Vashaee, Daryoosh
Abstract: Among various thermoelectric (TE) materials, iron disilicide (FeSi2 ) has relatively low cost and non-toxic characteristics which make it appropriate for large scale applications. To enhance the dimensionless figure of merit (ZT) of this material, a composite of FeSi2 –Si0.8 Ge0.2 with high fraction of α-FeSi2 was prepared by mechanical alloying and sintering. The process was followed by thermal annealing to transform α to β phase FeSi2 through a slow peritectoid reaction (several hours). The thermoelectric properties were significantly improved upon the completion of the phase transformation. At temperatures above 900 °C, FeSi2 component rapidly changed from β to α phase (several minutes) leading to sudden increase of the thermal conductivity. For comparison, the thermoelectric alloy of β-FeSi2 was prepared through a similar process. The effect of sintering conditions and annealing time were studied and a comparison was drawn between the thermoelectric properties of β-FeSi2 and FeSi2 –Si0.8 Ge0.2 nanocomposite. Overall, (FeSi2 )0.75 (Si0.8 Ge0.2 )0.25 showed 170% enhancement in ZT compared with β-FeSi2 making it suitable for medium to high temperature applications (500 °C −850 °C). Highlights: The composite of FeSi2 –Si0.8 Ge0.2 with high fraction of α-FeSi2 was synthesized. The α-FeSi2 transformed to β-FeSi2 through a slow peritectoid reaction. The thermoelectric properties were significantly improved after phase transformation. (FeSi2 )0.75 (Si0.8 Ge0.2 )0.25 showed 170% enhancement in ZT compared with β-FeSi2 . The composite was thermally stable with no dopant precipitation.